2006
DOI: 10.2139/ssrn.935106
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Information Systems in Collocated and Distributed Teams: A Test of the 24-Hour Knowledge Factory

Abstract: Acknowledgements: We appreciate the vision provided by Professor Lester Thurow, former Dean of the MIT Sloan School of Management, in highlighting the importance of outsourcing and the global economy, and the support provided by him at several stages of the research. We also acknowledge the help provided by a number of companies with respect to implementing the proposed vision in their respective companies. Author Biographies:Satwik Seshasai is the Development Manager for QuickPlace, IBM's enterprise team coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…In identifying which modes of social learning to examine, we found that social learning opportunities in teams may vary because of factors (Kleinbaum et al 2008) such as informal interactions (Marsick and Watkins 1997, Bobrow and Whalen 2002, Conlon 2004, social and cultural groups (Krishna et al 2004), and technology-mediated communication modes (Fulk and Boyd 1991, DeSanctis and Jackson 1994, Dede 1996, del Cerro et al 2001, Kreijns et al 2003, Smith 2003, Seshasai et al 2006. Across these situations, the following three modes reoccur as consistent patterns of actions, interactions and observations in social learning:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In identifying which modes of social learning to examine, we found that social learning opportunities in teams may vary because of factors (Kleinbaum et al 2008) such as informal interactions (Marsick and Watkins 1997, Bobrow and Whalen 2002, Conlon 2004, social and cultural groups (Krishna et al 2004), and technology-mediated communication modes (Fulk and Boyd 1991, DeSanctis and Jackson 1994, Dede 1996, del Cerro et al 2001, Kreijns et al 2003, Smith 2003, Seshasai et al 2006. Across these situations, the following three modes reoccur as consistent patterns of actions, interactions and observations in social learning:…”
Section: Introductionmentioning
confidence: 99%
“…What is required is an analysis of the configuration of social relations that permit social learning to affect team performance, which is mediated by the formation and disruption of TM. Knowing the relative contributions of the different modes of social learning will enhance our understanding of technology-mediated collaborative teamwork, which is known to support and limit the modes of interaction and communication, and hence, the modes of social learning (Fulk and Boyd 1991, DeSanctis and Jackson 1994, Dede 1996, del Cerro et al 2001, McDonough et al 2001, Kreijns et al 2003, Smith 2003, Seshasai et al 2006. Aside from the differential effect of various modes of social learning, there are factors that interfere with or attenuate its effects.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, even if the teams are flat for the purpose of task allocation, the opportunities for social learning are skewed owing to the physical boundaries (McDonough et al, 2001; Leinonen et al, 2005; Sutherland et al, 2007). Examples of distributed flat teams can be found in global product development teams (McDonough et al, 2001) and the current practice of outsourcing (Seshasai et al, 2006; Sutherland et al, 2007). Virtual teams can be considered as a kind of distributed team where it is possible that all the team members are distributed geographically such that there are no collocated clusters (Clancy, 1994; Desanctis & Monge, 1999).…”
Section: Conceptual Modelmentioning
confidence: 99%